Biodiversity of the coastal flora of Tripoli Province - Mahklouf, Mohammed H. (Biodiversity: Research and Conservation, 2020)
This study aims to investigate the coastal plant biodiversity status of Tripoli Province. The result of the survey led to a collection and identification of 130 plant species belonging to 36 families and 105 genera, of which 29 species represented monocotyledons and 101 dicotyledons. Floristic analysis revealed the dominance of the family Asteraceae (24 species) followed by the family Poaceae (22 species). The results have also showed the predominance of the genera Juncus and Lotus with 4 species each. Life form and chorological spectra analyses showed the prevalence of therophytes, represented by 77 species, and the Mediterranean chorotypes with 46 species. Categorization of collected plant species according to their ecological types, revealed a variety of ecological types, with the prevalence of psammophytes, represented by 50 species.